2018
DOI: 10.5897/ajb2017.16316
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antimicrobial and antifeedant activity of phenolic compounds accumulated in Hyoscyamus muticus L.

Abstract: Hyoscyamus muticus is an endangered desert plant spread in the Arabian Peninsula and the Middle East deserts. The methanol extract of the aerial parts of H. muticus grown in the arid zones in the Northern regions of Saudi Arabia were subjected to primary phytochemical analysis which revealed the presence of phenolic compounds, flavonoids, tannins and sterols, the gas chromatography-mass spectrometry (GC-MS) analysis of the methanolic extract exhibited different types of phenolic compounds, including ferulic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, it did not exhibit any activity against A. niger but was effective against several other fungi. In contrast, Elsharkawy et al 49 found that the methanolic extract of H. muticus aerial parts was successful in reducing the growth of S. aureus and Bacillus cereus . They also observed an inhibitory effect on E. coli , K. pneumoniae , and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 90%
“…However, it did not exhibit any activity against A. niger but was effective against several other fungi. In contrast, Elsharkawy et al 49 found that the methanolic extract of H. muticus aerial parts was successful in reducing the growth of S. aureus and Bacillus cereus . They also observed an inhibitory effect on E. coli , K. pneumoniae , and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the difference between the antioxidant activity of the extracts studied in this work and those from China could be due to the difference in their polyphenol, flavonoid, and tannin contents and experimental conditions (plant, standard, etc.). Indeed, many studies have previously mentioned that phenolic compounds have remarkable antioxidant properties in both in vitro and in vivo systems [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…According to the phytochemical analysis, methanol extract has the higher phenolic content, which demonstrates its effectiveness against the tested bacteria compared to aqueous extract. In fact, previous studies have been demonstrated the correlation between the antibacterial activity of plant extracts and its phenolic content (Rodríguez Vaquero et al 2010;Tomás-Menor et al 2013;Elsharkawy et al 2018).…”
Section: Antibacterial Activitymentioning
confidence: 99%